Home, School, Teachers and Personal Factors Affecting Numeracy Skills of Intermediate Grades at Buenasuerte Elementary School - Cañares, Shirley (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the factors affecting the numeracy skills of intermediate grade learners at Buenasuerte Elementary School. Anchored on Vygotsky’s Sociocultural Theory, Bruner’s Constructivist Theory, Bandura’s Social Cognitive Theory, and Gardner’s Multiple Intelligences Theory, the study investigated the influence of home-related, school-related, teacher-related, and personal-related factors on learners’ numeracy performance. A quantitative descriptive-correlational research design with a cross-sectional approach was employed. The respondents consisted of 64 Grade 4, Grade 5, and Grade 6 learners selected through purposive sampling from a population of 79 pupils. Data were collected using a researcher-adapted questionnaire and a researcher-developed numeracy test aligned with the Most Essential Learning Competencies (MELCs). Descriptive statistics and Pearson Product–Moment Correlation Coefficient were utilized to analyze the data. The findings revealed that the learners’ numeracy skills were generally at the Beginning level, indicating low mastery of fundamental mathematical competencies. Home-related, school-related, teacher-related, and personal-related factors all influenced numeracy skills to a moderate extent. Correlation analysis showed that school-related, teacher-related, and personal-related factors had significant positive relationships with numeracy skills, whereas home-related factors did not demonstrate a significant relationship. The results suggest that school support systems, instructional practices, and learners’ personal characteristics play important roles in numeracy development. The study concludes that strengthening school-based numeracy programs, effective instructional strategies, and learner motivation may contribute to improved numeracy outcomes. It recommends enhancing classroom practices, increasing access to learning resources, encouraging active learner participation, and sustaining parental support for mathematics learning. The study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting improved foundational numeracy skills and educational outcomes. It also supports SDG 10: Reduced Inequalities through efforts to identify barriers to learning and inform equitable educational interventions. The sustainability impact of the study lies in its contribution to educational, community, and institutional sustainability by providing evidence that can support effective numeracy programs, learner development initiatives, and collaborative efforts among schools, teachers, parents, and other educational stakeholders.
Keywords: Bangui–Dumalneg District; Elementary Learners; Literacy Development; Qualitative Research; Reading Difficulties; Reading Proficiency; School Leadership; Stakeholder Perspectives; Thematic Analysis; Transactional Theory of Reading